2020
DOI: 10.1074/jbc.ra120.014919
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-2 is post-translationally regulated by heme occupancy in the catalytic site

Abstract: Heme oxygenase-2 (HO2) and -1 (HO1) catalyze heme degradation to biliverdin, CO, and iron, forming an essential link in the heme metabolism network. Tight regulation of the cellular levels and catalytic activities of HO1 and HO2 is important for maintaining heme homeostasis. HO1 expression is transcriptionally regulated; however, HO2 expression is constitutive. How the cellular levels and activity of HO2 are regulated remains unclear. Here, we elucidate the mechanism of post-translational regulation of cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 58 publications
2
40
0
Order By: Relevance
“…S4 ), the sensor will not perturb the cellular biochemistry by depleting the availability of heme (forming a complex AH) as long as the total concentration of heme exceeds or equals 3 μM (the value reported in ref. 46 from denatured cell lysates). In this model, the total concentration of heme will include a minute fraction of free heme (estimated to be 5 nM; as in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S4 ), the sensor will not perturb the cellular biochemistry by depleting the availability of heme (forming a complex AH) as long as the total concentration of heme exceeds or equals 3 μM (the value reported in ref. 46 from denatured cell lysates). In this model, the total concentration of heme will include a minute fraction of free heme (estimated to be 5 nM; as in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of the holo form of the heme sensor, [AH], is shown in light red), where the total concentration of the expressed sensor, [A] 0 = [A] + [AH] is given on the horizontal axis ([A] = concentration of the apo form of the sensor). The model has been created by assuming that the total concentration of heme, [H] 0 = [H] + [BH] + [AH], is 3 μM ( 46 ); the concentration of free heme, [H], in the absence of a sensor or acceptor protein is 5 nM (as observed in Fig. 2 , Lower Left ); and the K d for heme dissociation from the sensor is 22 nM ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HO-2 binds heme at its catalytic site but also bears two additional heme binding sites termed heme regulatory motifs (HRMs), which contain Cys-Pro motifs [ 67 ]. In recent studies, mutation in the HRMs of HO-2 was found to accelerate HO-2 turnover via chaperone-mediated autophagy, suggesting that heme bioavailability regulates post-translational stability of HO-2 [ 68 ]. Ferric heme bound to HRMs may be reversibly transferred to the HO-1 catalytic site for degradation [ 69 ].…”
Section: Heme Degradationmentioning
confidence: 99%
“…Heme oxygenase 2 (HO-2) is expressed continuously in neurons and is not inducible (Chang et al, 2003 ). The regulation mechanism of HO-2 is not clear, however recent work by Liu et al ( 2020 ) demonstrated that HO-2 is stabilized by hemin. HO-2 carries three docking sites for heme but only one is catalytic, the remaining two are heme regulatory motifs that bind heme; unlike other heme-regulated proteins, HO-2 is only destabilized by a loss of heme binding to the catalytic site, not the regulatory sites (Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The regulation mechanism of HO-2 is not clear, however recent work by Liu et al ( 2020 ) demonstrated that HO-2 is stabilized by hemin. HO-2 carries three docking sites for heme but only one is catalytic, the remaining two are heme regulatory motifs that bind heme; unlike other heme-regulated proteins, HO-2 is only destabilized by a loss of heme binding to the catalytic site, not the regulatory sites (Liu et al, 2020 ). Heme oxygenase 1 (HO-1) is not expressed in the brain under normal circumstances but is expressed in macrophages (Naito et al, 2014 ; Vijayan et al, 2018b ), microglia (Schallner et al, 2015 ), and astrocytes localized to the peripheral tissue surrounding the hematoma from ICH (Chang et al, 2003 ; Yu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%